Literature Review of the Relationship Between Pain Perception and Coping in Mothers During Childbirth - Aryani, Hening Ryan (Health & Medical Sciences, 2025)
This study aims to explore the relationship between pain perception and maternal coping during childbirth through an in-depth qualitative literature review. The primary objective is to synthesize contemporary research findings to understand how physiological, and social factors interact in shaping women’s childbirth experiences. Using a qualitative descriptive approach, data were collected through a systematic review of scholarly books, peer-reviewed journal articles, and official reports published between 2015 and 2025. The analysis involved several stages—data identification, reduction, thematic categorization, and inductive interpretation—to uncover recurring concepts and relationships across the literature. The findings reveal that maternal self-efficacy, emotional support, and non-pharmacological interventions such as breathing exercises, massage, and music therapy significantly reduce perceived pain and enhance coping abilities. Conversely, fear and lack of confidence amplify pain perception and emotional distress. The study highlights the biopsychosocial nature of childbirth, aligning with theoretical frameworks such as Lazarus and Folkman’s stress-coping model and Olza’s neuro-psycho-social model of labor. The results underscore the importance of holistic, woman-centered maternity care that integrates emotional, social, and physical dimensions of childbirth. The research contributes theoretically by expanding understanding of pain-coping interactions and practically by recommending integrative care models that promote maternal empowerment and satisfaction. Future studies are encouraged to employ longitudinal and cross-cultural approaches to deepen insights into the evolving dynamics of coping during labor and postpartum adaptation.